2004
DOI: 10.7773/cm.v30i11.118
|View full text |Cite
|
Sign up to set email alerts
|

Allozymic variation in the Pacific oyster Crassostrea gigas from San Quintín Bay,Baja California, Mexico

Abstract: Allozymic variability was analyzed in adult oysters Crassostrea gigas from the 1999, 2000 and 2001 crops of San Quintín Bay, Baja California, Mexico, using starch gel electrophoresis. The analysis included 13 enzymatic systems that revealed 25 loci, of which 16 were monomorphic and 9 were polymorphic. The values of observed heterozygosis ranged from 0.01 to 0.04, while according to the literature, the value for wild oysters is approximately 0.20. The results indicate that there are no statistical differences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 10 publications
0
3
0
1
Order By: Relevance
“…Los homogenizados de los individuos se analizaron en electroforesis horizontal en geles de almidón al 10% (Sigma) utilizando la metodología descrita por de la Rosa-Vélez (1986) y Correa et al (2004). Se utilizaron los procedimientos de tinción histoquímica descritos por Abreu-Grobois (1983), de la Rosa-Vélez (1986), May (1992), Licona-Chávez (1999) y Correa et al (2004) para analizar un total de 23 sistemas enzimáticos, de los cuales se obtuvieron resultados reproducibles en 13 sistemas enzimáticos: malato deshidrogenasa (MDH, EC 1.1.1.37), enzima málica (ME, EC 1.1.1.40), isocitrato deshidrogenasa (IDH, EC 1.1.1.42), glucosa-6fosfato-1-deshidrogenasa (G6PDH, EC 1.1.1.49), superóxidodismutasa (SOD, EC 1.15.1.1), hexokinasa (HK, EC 2.7.1.1), carboxilesterasas (EST,, carboxilesterasas-D (EST-D, EC 3.1.1.1), fosfatasa alcalina (ALP,EC 3.1.3.1),leucilaminopeptidasa (LAP,EC 3.4.11.1),EC 5.3.1.8), fosfoglucosa-isomerasa (PGI, EC 5.3.1.9) y fosfoglucomutasa (PGM, EC 5.4.2.2). Con estos sistemas enzimáticos se obtuvieron un total de 21 loci.…”
Section: Análisis Electroforéticosunclassified
See 1 more Smart Citation
“…Los homogenizados de los individuos se analizaron en electroforesis horizontal en geles de almidón al 10% (Sigma) utilizando la metodología descrita por de la Rosa-Vélez (1986) y Correa et al (2004). Se utilizaron los procedimientos de tinción histoquímica descritos por Abreu-Grobois (1983), de la Rosa-Vélez (1986), May (1992), Licona-Chávez (1999) y Correa et al (2004) para analizar un total de 23 sistemas enzimáticos, de los cuales se obtuvieron resultados reproducibles en 13 sistemas enzimáticos: malato deshidrogenasa (MDH, EC 1.1.1.37), enzima málica (ME, EC 1.1.1.40), isocitrato deshidrogenasa (IDH, EC 1.1.1.42), glucosa-6fosfato-1-deshidrogenasa (G6PDH, EC 1.1.1.49), superóxidodismutasa (SOD, EC 1.15.1.1), hexokinasa (HK, EC 2.7.1.1), carboxilesterasas (EST,, carboxilesterasas-D (EST-D, EC 3.1.1.1), fosfatasa alcalina (ALP,EC 3.1.3.1),leucilaminopeptidasa (LAP,EC 3.4.11.1),EC 5.3.1.8), fosfoglucosa-isomerasa (PGI, EC 5.3.1.9) y fosfoglucomutasa (PGM, EC 5.4.2.2). Con estos sistemas enzimáticos se obtuvieron un total de 21 loci.…”
Section: Análisis Electroforéticosunclassified
“…The homogenates were analyzed by horizontal starch-gel (10%, Sigma) electrophoresis, following the methodology described by de la Rosa-Vélez (1986) and Correa et al (2004). The histochemical staining procedures described by Abreu-Grobois (1983), de la Rosa-Vélez (1986), May (1992), Licona-Chávez (1999) and Correa et al (2004) were used to analyze a total of 23 enzymatic systems, obtaining reproducible results for 13 of them: malate dehydrogenase (MDH, EC 1.1.1.37); malic enzyme (ME,EC 1.1.1.40); isocitrate dehydrogenase (IDH, EC 1.1.1.42); glucose-6-phosphate 1-dehydrogenase (G6PDH, EC 1.1.1.49); superoxide dismutase (SOD, EC 1.15.1.1); hexokinase (HK, EC 2.7.1.1); carboxylesterases (EST, EC 3.1.1.-); carboxylesterases-D (EST-D, EC 3.1.1.1); alkaline phosphatase (ALP, EC 3.1.3.1); leucil aminopeptidase (LAP, EC 3.4.11.1); manose-6-phosphate isomerase (MPI, EC 5.3.1.8); phosphoglucose isomerase (PGI, EC 5.3.1.9); and phosphoglucomutase (PGM, EC 5.4.2.2). A total of 21 loci were obtained with these enzymatic systems.…”
Section: Electrophoretic Analysismentioning
confidence: 99%
“…Industries such as aquaculture are currently operating in SQB at a sustainable rate (Aguirre-Muñoz et al 2001, Correa et al 2004, García-Esquivel et al 2004; however, the cover of Zostera marina meadows has declined by 14% (mainly in subtidal zones) over the last 2 decades (Ward et al 2004a,b). This habitat fragmentation reduces the size and increases the spatial isolation of plant populations, and decreases the effective population size thus leading to bottlenecks.…”
Section: Introductionmentioning
confidence: 99%
“…In Mexico, only two genetic studies of C. gigas have been made, both based on allozymes. De la Rosa-Vélez et al (1991) reported good genetic variability in cultures at San Quintín, Baja California, but more than 10 years later, Correa et al (2004) reported a severe reduction in variability at the same oyster farm. For C. corteziensis, Cruz et al (2007) The Marine Species Hatchery Center of the State of Sonora (Centro Reproductor de Especies Marinas del Estado de Sonora, CREMES) supplies more than 50 oyster farms in northwestern Mexico, providing spat of both diploid C. gigas and C. corteziensis.…”
Section: Introductionmentioning
confidence: 99%